ANALISIS KESALAHAN SISWA KELAS VIII SMPN 1 PARIAMAN DALAM MENYELESAIKAN SOAL MATEMATIKA BERDASARKAN NEWMAN’S ERROR ANALYSIS - Yony Utami (Jurnal Edukasi dan Penelitian Matematika, 2019)
This research aimed to describe types and factors of mistakes students in solving mathematical problems based on Newman's error analysis. The subject was students grade class VIII-5 in SMPN 1 Pariaman. Data obtained from the results of observations, tests and interviews. The data analysis according to miles dan Huberman, which was data reduction, data presentation, and making conclusion. The results of the research shows that students make mistakes in reading, comprehension, transformation, process skill and encoding. The factors that cause the error are students solve problems without looking at the questions first, students cannot understand the meaning conveyed by the problem, students are often given problems that has a linear equation, students are not careful writing the mathematical model, students do not check the answer that have been written, students do not master the material thoroughly, students do not pay attention to the teacher, the delivery of material from the teacher is sometimes too fast, students also do not dare ask to the teacher if they do not understand.Keywords – error analysis, Newman's error analysis, types and factors of error